ANALYSIS OF PUBLIC POLICY IN THE COVID-19 ERA IN CENTRAL KALIMANTAN PROVINCE - Erinda Alfiani Fauzi; Murniyati Yanur; Ester Sonya Ulfharitha Lapalu; M. Doddy Syahirul Alam; Dian Iskandar; Wijoko Lestariono; Bismar Harris Satriawan; Mahardiawan Putra (Universitas Pancasakti Tegal, 2023)
Public Policy in the COVID-19 era throughout Indonesia is experiencing changes, as is Central Kalimantan Province. Changes in Public Sector Management in Central Kalimantan occurred based on several regulations issued by the need for handling the COVID-19 virus. This research aims to analyze what policies have been implemented by Central Kalimantan Province in the COVID-19 era. The method used in this research is qualitative with literature study, with the data collection method being through documentation related to documents from magazines, newspapers, journals, etc., or through study books, as well as legal regulations related to research. The results of this research show that COVID cases in Central Kalimantan are increasing, resulting in large-scale social restrictions being implemented at all levels of government. After large-scale restrictions were implemented, public services and information were provided to the public on a limited basis and online by developing government applications and websites. Central Kalimantan Province has taken various measures to address the COVID-19 pandemic, but challenges continue. Efforts made during the pandemic must continue to be increased to maintain the health and welfare of the community and prepare ourselves to face similar situations in the future.